Ninth Five Year Plan (1997-2002) Draft Proposals Volume II (In Three Volumes) Haryana State - Planning Commission (Planning Commission, 1977)
Haryana Water Resources Consolidation Project The W.R.C.P. was necessitated to achieve the objectives of managing the total available water resources of the State efficiently and economically keeping in view the demand of the water users, ensuring equitable distribution of water amongst the beneficiaries by rehabilitating the existing canal & drainage works in the State for self sustaining of the department. With these objectives the studies were carried out in co-ordination consultations with World Bank before finalization of the W.R.C.P. costing Rs. 185825 Lakhs.(Rs. 136166.00 lakhs for works & Rs.49659.00 Lakhs for Estt The W.R.C.P. has stipulated execution period of six years w.e.f. 1994-95 to 1999-2000 to cover the project components of Modernization of existing Irrigation System and construction of new schemes such as Lining of Canals 4 Water courses etc. construction of Hathni Kund Barrage, Rehabilitation of Irrigation & Drainage System, Improving Operation & Maintenance (0 & M), Research & Development and Institutional Support.
Government of Haryana
Planning Department Government of Haryana
Keywords: Haryana Irrigation Department; Haryana Water Resources Consolidation Project; Project Components; Rehabilitation Of The Existing Canal & Drainage Systems; Modernization Of Canal System; Research and Development; Institutional Strengthening; Support For Operation & Maintenance Of Irrigation And Drainage System; Other Ongoing Projects; CONSTRUCTION OF SYL CANAL PUNJAB PORTION; GHARAUNDA IRRIGATION SCHEME; NALVI IRRIGATION SCHEME; Minor Irrigation and Tube well Corporation; Environmental Programmes.